1997
DOI: 10.1103/physrevlett.79.572
|View full text |Cite
|
Sign up to set email alerts
|

J/ψandψ(2S)Production inet al.

Abstract: We present a study of J/psi and psi(2S) production in p (p) over bar collisions, at root s = 1.8 TeV with the CDF detector at Fermilab. The J/psi and psi(2S) mesons are reconstructed using their mu(+)mu(-) decay modes. We have measured the inclusive production cross section for both mesons as a function of their transverse momentum in the central region, \eta\ < 0.6. We also measure the fraction of these events originating from b hadrons. We thus extract individual cross-sections for J/psi and psi(2S) mesons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 311 publications
(92 citation statements)
references
References 24 publications
3
88
0
1
Order By: Relevance
“…(2). The simulation includes, for the tracking chambers, a map of dead channels and the residual misalignment of the detection elements and, for the trigger chambers, an evaluation of their efficiency based on data.…”
Section: MCmentioning
confidence: 99%
See 1 more Smart Citation
“…(2). The simulation includes, for the tracking chambers, a map of dead channels and the residual misalignment of the detection elements and, for the trigger chambers, an evaluation of their efficiency based on data.…”
Section: MCmentioning
confidence: 99%
“…Results obtained for charmonium production at the Tevatron collider in the 1990s [2] led theory to recognize the role of intermediate quark-antiquark color-octet states in the production process, in the framework of the nonrelativistic QCD model [3]. This approach brought the calculations of p t spectra to agree rather well with the data [4] (p t is the transverse momentum, i.e., the momentum component perpendicular to the colliding beam direction).…”
mentioning
confidence: 99%
“…The J/ ψ production cross section measurements at the Tevatron [1, 2] were found to disagree by about a factor of 50 with theoretical color-singlet calculations [3]. Soon after, the CDF experiment reported a χ c2 / χ c1 cross section ratio that extended up to p T (J/ ψ )≃10 GeV/ c , where p T is the transverse momentum, and favored χ c1 production over χ c2  [4].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in collisions, the contribution of J=c associated production [8] was estimated to be several orders of magnitude smaller than the experimental data of J=c inclusive production [9]. In hadron collisions at the Tevatron, theoretical predictions [10,11] showed that the J=c þ c þ " c contribution was significant in the large p T region compared with the NLO result of non-c " c contributions, and the produced J=c is mainly unpolarized, which is analogous to the polarization of J=c in inclusive production [12,13]. The integrated cross section was also significant and showed a great measurable potential both at the Tevatron and Relativistic Heavy Ion Collider (RHIC).…”
Section: Introductionmentioning
confidence: 94%